Khronika natsional'noi politiki . Khronika natsional'noi politiki . Chronicle of National Politics . Хроника национальной политики - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Rehabilitation of repressed peoples; segment on Russian Koreans. Featured in the program: Reshul'skii, Sergei (Chairman of the Commission of the Nationalities Council of the Supreme Soviet of the Russian Federation) Реабилитация репрессированных народов, сюжет о российских корейцах. В программе участвуют: Решульский, Сергей (Председатель Комиссии Совета Национальностей Верховного Совета Российской Федерации по репрессированным и депортированным народам)